Efektifitas Relaksasi Benson terhadap Penurunan Nyeri Pasien Pasca Sectio Caesarea - Afnijar Wahyu (Jurnal Keperawatan Silampari, 2018)
The purpose of this study was to determine the relationship of the effect of Benson's relaxation on the reduction of the patient's pain in post-Caesarean section pain. This research method uses a quantitative method with a Quasi experimental design of One group Pre Test and Post Test with a sample of 22 people. The results of the study using Wilcoxon analysis showed p Value 0,000 p â‰¤0.05. The conclusion of this study is the effect of Benson's relaxation on the reduction of the pain of post-sectio caesarean pain in patients at Raja Ahmad Thabib Regional Hospital. Keywords: Benson Relaxation, Caesarean Sectio